Frequent accumulation of nuclear E-cadherin and alterations in the Wnt signaling pathway in esophageal squamous cell carcinomas. - Salahshor, S; Naidoo, R; Serra, S; Shih, W; Tsao, MS; Chetty, R; Woodgett, JR (2008)
Esophageal squamous cell carcinoma is frequently associated with poor prognosis, as a result of high levels of lymph node metastasis. So far, very few genetic abnormalities have been associated with this disease, and its molecular etiology remains largely unknown. To assess whether the Wnt pathway contributes to esophageal squamous cell carcinoma, we characterized the expression and subcellular localization of the key Wnt signaling components in all 30 cases of esophageal squamous cell carcinomas analyzed. We found abnormal expression and/or localization in glycogen synthase kinase-3 alpha/beta (34%), Axin2 (48%), alpha-catenin (31%), MYC (73%) and cyclin D1 in 46% of cases. Only 13% of tumors showed nuclear accumulation of beta-catenin. By contrast, 60% showed nuclear expression of E-cadherin using an antibody that recognizes the cytoplasmic domain of E-cadherin. When the same tumors were stained with antibody raised against the extracellular domain of E-cadherin, the expression was lost. A direct correlation was found between nuclear E-cadherin and the increased nuclear cyclin D1, one of the AP-1 target genes in these tumors. By transfection experiments, the cytoplasmic portion of E-cadherin was found to activate the AP-1 transcription factor pathway and induced cyclin D1 promoter activity, but beta-catenin/Tcf transcription activity was unaffected. Nuclear expression of E-cadherin was also detected in tumors other than squamous cell carcinoma, including pancreatic and colon cancers, albeit at lower frequency. Nuclear accumulation of a portion of E-cadherin in esophageal squamous cell carcinoma and the other types of tumors indicates that, in addition to the previously implicated tumor suppressor activity of E-cadherin, modified forms of this glycoprotein might also play a role in growth promotion.